The electrical and mechanical properties of Cadmium chloride reinforced PVA:PVP blend films - Rana S. Mahmood; Sabah A. Salman; Nabeel Ali Bakr (Papers in Physics, 2020)
In this study, pure polymer blend (PVA:PVP) film and salt (CdCl2·H2O) reinforced polymer blend films were prepared at different weight ratios (10 wt%, 20 wt%, 40 wt%) using the casting method. The effect of the salt weight ratio on the dielectric properties of the polymer blend films reinforced by CdCl2·H2O salt were investigated, and the experimental results showed that the dielectric constant and the dielectric loss factor decreased as the frequency increased for all polymer blend films. Moreover, the above-mentioned properties increased with increasing salt weight ratios at the same frequency. The experimental results also showed an increase in AC electrical conductivity with increasing frequency, for all polymer blend films, and the AC electrical conductivity also increased with an increase in the weight ratio of the salt at the same frequency. The effect of the salt weight ratio on the mechanical properties of the salt-reinforced PVA:PVP polymer blend films was also studied. The experimental results obtained from the tensile test of the salt-reinforced polymer blend films show significant change in the values of tensile strength, elongation at break, and Young’s modulus with increasing salt weight ratios; the hardness value first increases then decreases with increasing salt weight ratios, and the fracture energy value increases with increasing salt weight ratios, thus they could be good candidates for hard adhesives with low flexibility.